Transaction cost as a basis for deciding on marketing channels in the rural meat markets of the northern communal areas of Namibia - De Bruyn, Pietersarel (Stellenbosch : Stellenbosch University, 2012)
Thesis (MAgricAdmin)--Stellenbosch University, 2002.